Adherence to medication and physical activity among people living with HIV/AIDS - Mohammad-Ali Morowatisharifabad; Ehsan Movahed; Rohollah Nikooie; Jamileh Farokhzadian; Reza Bidaki; Mohsen Askarishahi; Mahdieh Hosseinzadeh (Wolters Kluwer Medknow Publications, 2019)
Background: The aim of this study was to investigate the adherence to medication and Physical Activity (PA) among People Living with HIV (PLHIV). Materials and Methods: In the present cross-sectional study, 122 PLHIV were selected. The research tools included the Baecke questionnaire and the AIDS Clinical Trials Group questionnaire. Data were analyzed by independent t test and multiple logistic regression. Results: The results of 7- and 30-day recalls showed that 76.21 and 82.23% of patients had proper medication adherence. The mean score of PA in patients was less than the recommended average score in the questionnaire. Furthermore, there was no significant difference observed between the medication adherence and PA. Conclusions: Although the adherence to medication was appropriate, nurses and health care providers should increase the level of PA for PLHIV by dealing with the related barriers to live an active life.